Governmental Crisis Communication for Tourism Recovery: Lessons from Bandar Lampung in the Covid-19 Era - Aji, Jaya; Zainal, Anna Gustina; Wardhani, Andy Corry; Trenggono, Nanang (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
The COVID-19 epidemic significantly impacted the worldwide tourism sector, resulting in a notable decrease in both domestic and foreign tourist arrivals in Bandar Lampung. The Bandar Lampung Tourism Office, as the principal institutional authority managing the city's tourism sector, was necessitated to react swiftly and efficiently to a developing issue. This study examines the crisis communication management tactics employed by the office during the pandemic. This research adopts a post-positivist perspective and utilizes a qualitative, descriptive technique to analyze crisis communication during three essential phases: pre-crisis, crisis, and post-crisis. The results demonstrate that the pre-crisis timeframe was marked by inadequate preparedness and a lack of proactive risk mitigation strategies. The crisis phase demonstrated a more nimble institutional response, characterized by adaptive methods, intersectoral collaborations, and innovation-driven modifications to tourism operations. During the post-crisis period, the Tourism Office implemented communicative techniques aligned with the Situational Crisis Communication Theory (SCCT), encompassing image restoration, stakeholder reassurance, and strategic media framing to influence public opinion and restore trust. These observations enhance the broader discussion on crisis communication in the public sector and emphasize the necessity for robust, theory-based frameworks in tourist governance during global shocks.